MANNOSYLATED MULTIWALLED CARBON NANOTUBES ASSISTED ARTESUNATE DELIVERY FOR CEREBRAL MALARIA: MULTIWALLED CARBON NANOTUBES ASSISTED ARTESUNATE DELIVERY - Gulbake, Anamika Sahu; Jain, Aviral; Shilpi, Satish; Kumar, Pramod; GULBAKE, ARVIND (International Journal of Applied Pharmaceutics, 2019)
Objective: The present investigation focused on the novel approach using artesunate (AS) loaded mannosylated conjugated multi-walled carbon nanotubes (M-MWCNTs) for site-specific delivery to the brain in the treatment of cerebral malaria (CM). Methods: The raw MWCNTs were purified by selective oxidation method and then exposed to sequential chemical functionalization according to the following steps: carboxylation, acylation, amine modification and finally, D-mannose conjugation. The AS was loaded via the equilibrium dialysis method in the molar ratio 1:3 of various functionalized sonicated MWCNTs. The functionalized MWCNTs were characterized for elemental analysis, FTIR, TEM, zeta potential and percentage drug entrapment efficiency. The in vitro drug release study was performed on AS conjugated purified MWCNTs (AS-P-MWCNT) and AS conjugated M-MWCNTs. Bio-distribution study was performed on albino rat for quantitative measurement of AS in different organs and blood. Results: The TEM images of M-MWCNTs indicated their open tubular nature and AS-M-MWCNTs suggests the entrapment of AS. The percent drug entrapment of AS-M-MWCNT was found to be 80.29±3.4 %. In vitro AS release from AS-M-MWCNTs was found in a controlled manner at pH 7.4. The bio-distribution studies clearly indicate the superiority of the AS-M-MWCNTs, as compared to the plain drug towards increasing the accumulation of AS in brain. Conclusion: The results suggest that AS-M-MWCNTs could be employed as an efficient nano-carrier for antimalarial therapy in cerebral malaria.